DEVELOPING STUDENTS’ SKILLS IN LEARNING FOREIGN LANGUAGES - Narziyeva Nargiza Ravilevna (TADQIQOTLAR, 2026)
This article explores methods and strategies for developing students’ skills in learning foreign languages. It emphasizes the importance of communicative competence, cognitive development, and motivation in the language learning process. The study highlights practical approaches, including interactive activities, multimedia resources, and task-based learning, to enhance students’ proficiency and confidence in using a foreign language.